YELLOW FEVER: A WORD THAT EVOKES MEMORIES OF SUFFERING IN ITALIAN IMMIGRANTS FROM BRAZIL - Babini, Maurizio; Barros, Lídia Almeida (Seven Editora, 2025)
Yellow fever is still one of the most widespread diseases in tropical countries. Thanks to the discovery of a vaccine, which occurred in 1937, the number of deaths due to this disease reduced enormously. However, by the time mass vaccinations began, it had caused numerous epidemics and killed hundreds of thousands of human beings. European immigrants who arrived in Brazil were exposed to this disease, and in many cases it tragically interrupted the hope of a better future. The main objective of this work is to show the importance of yellow fever in the collective imagination of Italian immigrants who came to Brazil. In the first part of our work, we will show a brief history of this disease and its current diffusion. Subsequently, we will see, through historical reports and documents, the impact that this disease had on the migratory movements of Italians who came to Brazil, and how it marked their collective imagination, leaving memories of fear and suffering. DOI: https://doi.org/10.56238/sevened2024.037-125